Caribbean Report 27-09-1995 - Ransome, Debbie (anchor); Jagan, Cheddi (interviewee); Donnelly, Brian (interviewee); Valley, Kenneth (interviewee); Fletcher, Pascal (correspondent); Jarvis, Mike (correspondent); Seaga, Edward (interviewee); Orr, Carol (correspondent); Rodney, Karl (interviewee) (The British Broadcasting Corporation, 1995)
In this report, Guyana's President Cheddi Jagan states he is pressing ahead to obtain as quickly as possible a report from a commission of inquiry into the cyanide spill at the Omai Goldmines. In Washington, the NAFTA Parity Bill to give the Caribbean equal arrangement with NAFTA was dropped. However, US Ambassador, Brian Donnelly comments that the bill has not been completely lost. Trinidad and Tobago plans to step up investment in Cuba and proposes a trade mission in the near future. Ambassador Donnelly argues that this does not change Trinidad's relationship with the US. Environment Ministers from Latin America and the Caribbean oppose the US embargo on Cuba, at a regional meeting. Cuba argues that the US embargo has directly affected its ability to tackle environmental problems. Meanwhile, the fourteenth storm of this turbulent hurricane season, tropical storm Noel will veer away from the region. Hurricane-affected St. Martin puts its recovery efforts in high gear as costs could spiral unless they capture a part of the vital winter tourist season. The Jamaica Labour Party (JLP) Leader Edward Seaga accuses former party Chairman Bruce Golding of promoting the JLP's positions as his own in a bid to form a third political party. British tabloid press has been paying attention to Colin Powell's white heritage as the black media examines his Caribbean roots amid speculation that he will make a bid for the White House.
1. Headlines with Debbie Ransome (00:00-00:40)
2. Guyana's President Cheddi Jagan pushes for a quick outcome from an inquiry into the Omai Goldmines cyanide spill (00:41-04:07)
3. The bill to give the Caribbean equal arrangement with NAFTA has been put aside (04:08-06:01)
4. Trinidad and Tobago plans to improve trade links with Cuba and the local US Ambassador is asked about possible American censure (06:02-07:45)
Keywords: Governmental investigations -- Guyana; Pollution -- Environmental aspects -- Guyana; Cyanide wastes -- Essequibo River (Guyana); Free trade -- North America; Trinidad and Tobago -- Commercial policy; Trinidad and Tobago -- Foreign relations -- Cuba; Cuba -- Foreign relations -- Trinidad and Tobago; Investments -- Cuba; Economic sanctions, American -- Cuba; Environmental policies -- Caribbean Area; Environmental policies -- Latin America; Cuba -- Environmental conditions; Hurricanes -- Caribbean Area; Hurricane damage -- Saint Martin; Tourism -- Saint Martin; Politicians -- Jamaica; Political parties -- Jamaica; Jamaica -- Politics and government; African American generals -- United States; Mass media and race relations -- Great Britain; African American -- Race identity -- United States